Temperature-dependent rate coefficients for the reactions of OH radicals with selected alkanes, aromatic compounds, and monoterpenes - F. Berg; A. Novelli; R. Dubus; A. Hofzumahaus; F. Holland; A. Wahner; H. Fuchs; H. Fuchs (Atmospheric Chemistry and Physics)
The rate coefficients of the reaction of hydroxyl radicals (OH) with 12 different volatile organic compounds (VOCs), namely methane, ethane, propane, n-butane, methyl vinyl ketone (MVK), γ-terpinene, Δ3-carene, myrcene, toluene, o-xylene, m-xylene, and mesitylene, were studied in an absolute rate study in 1 atm of air between 280 and 340 K using an OH reactivity instrument with a temperature-controlled flow tube. There are few or no measurements in the literature for the important monoterpene and aromatic compounds emitted by biogenic and anthropogenic sources, although the oxidation of these species is particularly important in the formation of secondary pollutants such as ozone and particles. The time-dependent decay of the OH concentration was measured in a flow tube, allowing the pseudo-first-order rate coefficient to be determined after the production of a moderately high OH concentration (about 1×109 cm−3) by the photolysis of ozone in the presence of water vapour. In contrast to many previous studies, the OH reaction took place in a volume at ambient conditions, while the detection of OH was achieved by fluorescence in a separate low-pressure detection volume. The VOC concentrations were measured using the total organic carbon method. With the methods used, a high accuracy of the rate constants is obtained (2σ uncertainties approximately 6 %).